Kualitas Pelayanan Akademik terhadap Kepuasaan dan Loyalitas Mahasiswa - Anwar, Wafiq Fadhilah; Malik, Adam; Ayuna, Nadia; Dewi, Anggun Kurnia (J-MPI (Jurnal Manajemen Pendidikan Islam), 2023)
The relationship between the quality of services provided by higher education institutions and consumer satisfaction is very close. This quality can motivate students to form a strong bond with the university and build loyalty towards it. The purpose of this research is to examine the influence of service quality on student satisfaction and loyalty. The subjects of this study are graduate students in the Islamic Education Management Department at UIN Sunan Gunung Djati Bandung. A quantitative method is employed in this research with a sample size of 76 individuals determined through the Slovin formula and purposive sampling method. The results of the study indicate that service quality significantly affects student satisfaction (Y1). Service quality, as the X variable, also significantly influences student loyalty (Y2). Further understanding of the positive correlation between service quality and student loyalty can assist universities in designing student retention programs and building a committed community on campus. These implications support efforts to enhance the quality of higher education services and establish a sustainable relationship between universities and students.